Clinical Remission of Sight-Threatening Non-Infectious Uveitis Is Characterized by an Upregulation of Peripheral T-Regulatory Cell Polarized Towards T-bet and TIGIT - Gilbert, Rose M.; Zhang, Xiaozhe; Sampson, Robert D.; Ehrenstein, Michael R.; Nguyen, Dao X.; Chaudhry, Mahid; Mein, Charles; Mahmud, Nadiya; Galatowicz, Grazyna; Tomkins-Netzer, Oren; Calder, Virginia L.; Lightman, Sue (Frontiers in Immunology, 2018)
Background Non-infectious uveitis can cause chronic relapsing and remitting ocular inflammation, which may require high dose systemic immunosuppression to prevent severe sight loss. It has been classically described as an autoimmune disease, mediated by pro-inflammatory Th1 and Th17 T-cell subsets. Studies suggest that natural immunosuppressive CD4+CD25+FoxP3+ T-regulatory cells (Tregs) are involved in resolution of inflammation and may be involved in the maintenance of clinical remission. Objective To investigate whether there is a peripheral blood immunoregulatory phenotype associated with clinical remission of sight-threatening non-infectious uveitis by comparing peripheral blood levels of Treg, Th1, and Th17, and associated DNA methylation and cytokine levels in patients with active uveitic disease, control subjects and patients (with previously active disease) in clinical remission induced by immunosuppressive drugs. Methods Isolated peripheral blood mononuclear cells (PBMC) from peripheral blood samples from prospectively recruited subjects were analyzed by flow cytometry for CD3, CD4, FoxP3, TIGIT, T-bet, and related orphan receptor γt. Epigenetic DNA methylation levels of FOXP3 Treg-specific demethylated region (TSDR), FOXP3 promoter, TBX21, RORC2, and TIGIT loci were determined in cryopreserved PBMC using a next-generation sequencing approach. Related cytokines were measured in blood sera. Functional suppressive capacity of Treg was assessed using T-cell proliferation assays. Results Fifty patients with uveitis (intermediate, posterior, and panuveitis) and 10 control subjects were recruited. The frequency of CD4+CD25+FoxP3+ Treg, TIGIT+ Treg, and T-bet+ Treg and the ratio of Treg to Th1 were significantly higher in remission patients compared with patients with active uveitic disease; and TIGIT+ Tregs were a significant predictor of clinical remission. Treg from patients in clinical remission demonstrated a high level of in vitro suppressive function compared with Treg from control subjects and from patients with untreated active disease. PBMC from patients in clinical remission had significantly lower methylation levels at the FOXP3 TSDR, FOXP3 promoter, and TIGIT loci and higher levels at RORC loci than those with active disease. Clinical remission was also associated with significantly higher serum levels of transforming growth factor β and IL-10, which positively correlated with Treg levels, and lower serum levels of IFNγ, IL-17A, and IL-22 compared with patients with active disease. Conclusion Clinical remission of sight-threatening non-infectious uveitis has an immunoregulatory phenotype characterized by upregulation of peripheral Treg, polarized toward T-bet and TIGIT. These findings may assist with individualized therapy of uveitis, by informing whether drug therapy has induced phenotypically stable Treg associated with long-term clinical remission.